Implikasi Media Baru Sebagai Media Komunikasi Dan Teknologi Informasi - Ida Ayu Nadia Varenia; Ida Bagus Yudha Phalguna (Sadharananikarana: Jurnal Ilmiah Komunikasi Hindu, 2022)
New media is a term to describe the convergence of digital communication technology that is computerized and connected to a network and cannot be separated from the use of information technology, both network-based and telecommunications. as an example of media that is very representative of new media is the internet. New media is present as a new medium of communication at this time. All the ease of access provided by new media began to shift conventional media as communication media. This study aims to determine the implications of new media as a medium of communication and information technology. The implications of new media as a medium of communication By using new media it is easier for the audience to access things, such as news information that can be accessed in real time, the ease of exchanging information with relatives only by using internet-based devices. The internet is also a form of change in new media. However, the presence of new media as a medium of communication in this era in addition to providing positive implications also has negative implications. The implication of the presence of new media as a communication medium is that with the presence of new media, people's dependence on old media has begun to be replaced by a more real time, effective media, this is one of the positive sides of the new media as communication media and information technology. On the other hand, the negative implication of the presence of new media is that it often results in humans themselves forgetting and ignoring the real world and actually paying more attention to the virtual world, besides that new media are vulnerable to users, especially if new media is consumed by children without adult supervision.